Caloric test and video head impulse test sensitivity as vestibular impairment predictors before cochlear implant surgery (Clinics, 2019)
OBJECTIVES: Currently, cochlear implant procedures are becoming increasingly broad and have greatly expanded. Bilateral cochlear implants and cochlear implants are more frequently applied in children. Our hypothesis is that the video head impulse test may be more sensitive than the caloric test in detecting abnormal vestibular function before cochlear implant surgery. The objective of this study was to compare the video head impulse test and caloric test results of patients selected for cochlear implant procedures before surgery. METHODS: The patients selected for cochlear implant surgery were submitted to a bithermal caloric test and video head impulse test. RESULTS: By comparing angular slow phase velocity values below 5o in the bithermal caloric test (hypofunction) and video head impulse test with a gain lower than 0.8, we identified 37 (64.9%) patients with vestibular hypofunction or canal paresis and 21 (36.8%) patients with abnormal video head impulse test gain before the cochlear implant procedure. Of the 37 patients with caloric test vestibular hypofunction, 20 (54%) patients exhibited an abnormal gain in the video head impulse test. CONCLUSION: The caloric test is more sensitive than the video head impulse test (Fisher’s exact test, p=0.0002) in detecting the impaired ear before cochlear implant delivery. The proportion of caloric test/video head impulse test positive identification of abnormal vestibular function or caloric test/video head impulse test sensitivity was 1.8:1.